The Development of Inquiry Learning Model on Indonesian Language Lessons - Pohan, Jusrin Efendi (Universitas Malikussaleh, 2019)
This study aims to produce an inquiry learning model on Indonesian subjects. This model emphasizes the discovery of meaning contained in a text. This inquiry learning model was developed through the Plomp model (2013) which consisted of the preliminary research stage, the prototype stage, and the assessment stage. This model is validated by experts in terms of substance aspects, presentation, language, and graphics. This model was tested in class XII of SMA Negeri 1 Padang Bolak to see the practicality and effectiveness. This study shows that the inquiry learning model in Indonesian language subjects in class XII of SMA Negeri 1 Padang Bolak is valid, practical, and effective. The validity of the inquiry learning model seen from the results of content validation and constructs with a score of 3.70 is a very valid category. The practicality of the inquiry learning model can be seen from the results of the practical sheet filled by students of 84.5 with a very practical category, while the effectiveness of the inquiry learning model seen from the increase in student learning outcomes by 94.65 in the very effective category.